An Analysis of Indirect Speech Act in The Eternals Movie : - - Islam, Nurul; Al Fauzi, Fatih; sabartono, Ribut (E-Link Journal, 2025)
Language is a tool to communicate with each other. To make beginners understand about English, they must use media to learn. films were chosen to analyze the importance of educational values as part of our lives. Speech acts are crucial for individuals who desire to speak on their own in a particular circumstance. When a speech act occurs, it has a meaning and an objective. People who do speech acts don't just make sounds; they also perform it into actions. This study discusses the use of Indirect Speech acts in the conversations of Eternals movie characters. The purpose of this research is to find out the forms and functions of indirect speech acts performed by the characters in the film Eternals. The methodology used in this study is a qualitative descriptive method, in which the researcher collects data from scripts and dialogues, then determines the form and function of the indirect speech performed by the characters and classifies illocutionary acts based on Searle's theory.To focus on this research, the results of this study are that the researcher found 10 data on forms of indirect speech acts and the researcher found two forms of indirect speech acts which are interrogative, declarative which are used in the film Eternals and there are 2 values/morals that can be taken in the film Eternals. Thus the conclusion is obtained : Finally, this study concludes that indirect speech acts have different forms but have different meanings. Situational context and social status are very important in the use of indirect speech. In this study also provides suggestions for the perfection of further research and closing is the end of this research report.